Acute Motor Conduction Block Neuropathy: Another Distinct Variant of Guillain-Barre Syndrome - ERDOĞMUŞ İNCE, Nilüfer (Noro Psikiyatr Ars, 2014)
We describe a patient who developed progressive weakness in all limbs without sensory symptoms 4 weeks after upper respiratory system infection. Electrophysiological findings suggested a new variant of Guillain-Barré syndrome named “acute motor conduction block neuropathy”. Electrophysiological studies were performed at admission, 12(th) and 28(th) weeks. At the 28(th) week, the clinical examination and electrophysiological findings showed complete recovery.